Prevalence Of Forward Head Posture Among University Students And Its Association With Smartphone Screen Time: Validation Of The Smart Protector App For Craniovertebral And Craniohorizontal Angle Measurement - Yogita, Yogita; Singh, Reetika; Pandya, Tanuja; Jain, Kapila; Duhan(PT), Manila; Sidhant, Sidhant (Journal of Neonatal Surgery, 2025)
Objective: The research demonstrates the widespread occurrence of forward head position among university students. Research will determine how common forward head posture is and how it relates to mobile-device utilization. The smartphone application functions as a measurement tool for forward head posture evaluation. The evaluation of forward head position will occur through the smart protector tool application. Background: Forward head posture functions as an epidemic which has significantly increased since the current technological period initiated. A clinical diagnosis characterizes this condition as when the head rests ahead of its normal position relative to the shoulder point. Forward movement of the human gravity axis occurs when the head tilts forward. When the upper body shifts backward toward reclining posture with shoulder slumping the head moves in front of the trunk. Design: Survey method Method: Subjects received information about the study and researchers explained the research objectives to them. The research study included 72 participants who were young student volunteers and symptom-free. The smart protector tool application measured both Craniovertebral angle and Craniohorizontal angle. Mobile phone users recorded their screen time as 2 weeks on average. Result: Result shows that due to less awareness about proper posture maintenance forward head posture is increased in young students. According to CVA angle 26.4% students and CHA 4.2% subjects had forward head posture. And smart protector tool application is a reliable tool for measuring craniohorizontal and craniovertebral angles to assess forward head posture. Conclusion: FHP occurs frequently amongst young age learners, so smart protector tool provides a suitable method to assess posture through craniovertebral and craniohorizontal angle measurements from photographs.